Combatting the Danger of a Single Story: Empirical Comparison of Resource Availability among Ibadan Rural and Urban Pre-School Centers, Nigeria - Olalowo, Iyanuoluwa Emmanuel; Salami, Ishola Akindele (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
Learning in the early years of life is not just an intra-personal effort of the child alone; rather, it involves the interplay of several social factors, which can affect a child’s development. However, literature that considered and presented these factors as obtainable within preschools mostly revealed their facts and figures in a single story of either urban or rural preschools, cheering an uneven intervention from developmental agencies afterward. This study sought to provide an empirical comparison of the state of preschool resources in Ibadan rural and urban communities. A descriptive survey research design was adopted. The population includes public preschool centers in Ibadan. A proportionate stratified sampling technique was used to select 20% of the preschools from two selected local governments of Ibadan which represent the urban and rural communities. A total sample of 33 preschools was used. Data was collected using Pre-primary School Resources Availability Checklist (PREPSRAC, r = 0.89). Findings were that classroom resources are more available in urban preschools compared to rural pre-primary schools of Ibadan contrary to generalized remarks. Equity rather than equality of resources distribution is therefore recommended as a way of discontinuing the danger of a single story in pre-primary education for promoting equal learning.